2018
DOI: 10.1080/14740338.2018.1499724
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Twitter as a complementary data source for pharmacovigilance

Abstract: With the use of dedicated tools, Twitter could become a complementary source of information for pharmacovigilance, despite a major limitation regarding causality assessment of ADRs in individual tweets, which may improve with the new limitation to 280 characters per tweet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…For instance, we considered tweets written in Spanish and from public Twitter users' timelines, and these users may be not representative of the general population or people suffering from depression [33,49,78,79]. Some studies have shown that Twitter users are often urban people with high levels of education, and they are generally younger than the general population [33,49,78,80,81]. We should also take into account that SSRIs are used in different types of depressive disorders and in other mental conditions.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, we considered tweets written in Spanish and from public Twitter users' timelines, and these users may be not representative of the general population or people suffering from depression [33,49,78,79]. Some studies have shown that Twitter users are often urban people with high levels of education, and they are generally younger than the general population [33,49,78,80,81]. We should also take into account that SSRIs are used in different types of depressive disorders and in other mental conditions.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Another limitation may be the fact that Twitter users who share their personal drug intake may use words or expressions not included in the list of drug names employed in this study for streaming tweets, even though we tried to be exhaustive in the list of names used. Twitter texts are informal and limited by the number of characters, and they commonly include abbreviations, errors, or slang language [33,45]. All these issues can make it difficult to automatically extract drug mentions and link them to a formal lexicon [28,30,50,53,55].…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…This body of science spans a number of disparate areas, including tracking the spread of influenza [ 3 , 4 ], oral health problems [ 5 ], sleep issues [ 6 ], obesity [ 7 ], cardiovascular disease [ 8 ], diabetes [ 9 ], mental health [ 10 ], and health care enrollment [ 11 ]. In addition, there is burgeoning interest in the use of innovative and nontraditional methods (such as mining and analyzing social media data) as a means to better surveil the opioid epidemic, with Twitter becoming a complementary data source for pharmacovigilance [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%